(untitled) (Repertorio Científico, 2024)
An evaluation of land use was carried out in one of the cultivated farms downstream of the Pirrís River reservoir, in order to evaluate the contribution of polluting loads to the river bed. The foregoing was carried out through a premonitory of sedimentation for 16 weeks and 2 laboratory tests of agents associated with agricultural activity. One study was carried out in the summer-winter transition period and the other in winter, with the aim of having a capacity to dilute polluting agents. As the Los Santos region is a geographically vulnerable area to water erosion, due to the constant rainfall during the winter season, the study area was located on the course of this river. This study sought to show how two different production scenarios contribute or not to surface dragging of sediments and what kind of Good Agricultural Practices are carried out on farms to mitigate damage. Once the project was completed, it was concluded that there is an absence of BPA on the evaluated farm, facilitating the dragging of sediments, as well as alterations to the water quality of this basin In the end, it is recommended to carry out the chemical analyzes on a monthly basis to prevent the pesticide molecules from degrading and dissipating as a result of their high solubility in water and also to carry out a chemical analysis of the water with sediments captured in the drawers at the farm level in order to obtain better results.